FACTORS ASSOCIATED WITH COMORBIDITIES AMONG DIABETIC PATIENTS OF JINJA REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - Alimwenda, Violet; Kajubi, Richard; Atuhaire, Hilary; Anahita, Ali (SJ Insights, 2025)
Background Comorbidity is the occurrence of more than one chronic illness in a patient and can potentially make medical management complicated. The study aims to assess the factors associated with comorbidities among diabetic patients of Jinja Regional Referral Hospital. Methodology A descriptive cross-sectional study that employed quantitative data techniques was used. Simple random sampling was used to select participants in the study. Descriptive statistics was used to assess the frequency distribution of the three risk categories. A Chi-square test assessed the categorical variables and trends in the prevalence of diabetic comorbidities. Results The number of patients who had DM for less than 5 years was 92(32.4%) and for more than 5 years was 192(67.6%). The number of patients who were smoking was 32(11.3%) and 113(39.8%) were taking alcohol. In bivariate analysis, using chi-square tests for categorical variables and the Fishers Exact test where the chi-square assumptions were not fulfilled, a statistically significant relationship was found between age (OR=0.954, P=0.07), sex, (OR=02.194, P=0.019), type of DM(OR=0.464, P=0.015), smoking (OR=0.533, P=0.036), cholesterol level (OR=2.640, P=0.003). There was no statistical significance found between the type of treatment (OR=0.662, P=0.521), duration of DM (OR=0.8662, P=0.705), HIV status (OR=1.252, P=0.558), physical activity (OR=1.798, P=0.106), alcohol (0R=0,743, P=0.334) and BMI (OR=0.712, P=0.165) Conclusion Age, place of residence, and type of DM were the predominant factors associated with diabetes comorbidity. Recommendations The government should also establish care models that bring together healthcare providers, patients, and families to manage diabetes and its comorbidities.